# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime } = -a^{2} y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-k^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }-54 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-m^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+5 y^{\prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }+18 y^{\prime }-16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}a y^{\prime \prime } = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-n^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{\prime \prime }+5 x^{\prime }-12 x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }-54 y = 0
\] |
✓ |
✓ |
|
\[
{}9 x^{\prime \prime }+18 x^{\prime }-16 x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-a^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}a y^{\prime \prime } = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+9 y^{\prime }-18 y = 0
\] |
✓ |
✓ |
|